Differential transcription directed by discrete gamma interferon promoter elements in naive and memory (effector) CD4 T cells and CD8 T cells. - Aune, T M (1997)
Acquisition of the ability to produce gamma interferon (IFN-gamma) is a fundamental property of memory T cells and enables one subset (T helper 1 [TH1]) to deliver its effector functions. To examine regulation of IFN-gamma gene expression in a model system which recapitulates TH1 differentiation, we prepared reporter transgenic mice which express the luciferase gene under the control of proximal and distal regulatory elements (prox.IFN gamma and dist.IFN gamma) from the IFN-gamma promoter. Memory T cells, but not naive T cells, secreted IFN-gamma and expressed both prox.IFN gamma and dist.IFN gamma transcriptional activities. Naive T cells required priming to become producers of IFN-gamma and to direct transcription by these elements. While both CD4+ and CD8+ T cells produced IFN-gamma, only CD4+ T cells expressed prox.IFN gamma transcriptional activity. Induction of transcriptional activity was inhibited by known antagonists of effector T-cell populations. Cyclosporin A inhibited transcriptional activity directed by both elements in effector T cells. Elevated cyclic AMP inhibited transcriptional activity directed by prox.IFN gamma in primed CD4+ T cells but enhanced transcriptional activity directed by dist.IFN gamma in primed CD8+ T cells. Taken together, these data show that prox.IFN gamma and dist.IFN gamma transcriptional activities mirror IFN-gamma gene expression in naive and memory CD4+ T cells but suggest that differences exist in regulation of IFN-gamma gene expression in CD4+ and CD8+ T-cell subsets.